Strengthening Family Welfare through the Empowerment of Women-Owned MSMEs in Aceh Besar Regency - Rahmah Yulianti; Abubakar; Bukhari Usman; Hafidh Maksum; Anwar; Filia Hanum (Ilomata International Journal of Tax and Accounting, 2026)
Women’s economic empowerment through micro, small, and medium enterprises (MSMEs) is widely recognized as an important strategy for supporting household livelihoods and local economic resilience. However, women entrepreneurs continue to face structural and socio-cultural constraints, particularly in rural contexts. This study aims to explore how women-owned MSMEs are experienced in relation to family welfare and how empowerment is shaped by Islamic values and local wisdom in Aceh Besar Regency. This study employed a qualitative field research approach. Data were collected through semi-structured interviews, observations, and documentation involving 12 women MSME actors selected using purposive sampling. Participants were aged 20–45 years, engaged in culinary, handicraft, and small-scale retail businesses, with business experience ranging from 1 to 10 years. Each interview lasted approximately 45–60 minutes. Data were analyzed using the interactive model of Miles, Huberman, and Saldana. The findings suggest that participants reported contributing to household income, particularly in meeting daily needs and supporting children’s education. MSME activities were also described as helping households manage financial uncertainty. Participants indicated that Islamic values, such as honesty, fairness, and avoidance of riba, along with local practices such as community cooperation, influenced business practices and supported customer trust. At the same time, participants reported ongoing challenges, including limited access to capital, markets, and technology. These findings suggest that women’s involvement in MSMEs is perceived as meaningful for household welfare, while also being shaped by broader structural and socio-cultural contexts.